Undang-Undang Melaka Suatu Tinjauan Resepsi dan Interteks (Undang-Undang Melaka A Reception and Intertextual Approach) - Taufiq Ahmad Dardiri (Al-Jami'ah: Journal of Islamic Studies, 1991)
This research takes object of the text of Undang-Undang Melaka, issued in critical edition by Liaw Yock Fang (1976). This text is wellknown as Undang-Undang Negeri Melaka, Risalah Hukum Kanun, Hukum Kanun, and Undang-Undang Melayu.  The text is known as one of the oldest and the most important Indonesian literature which contain laws. because of the wide application and the great amount of its manuscripts and also of the variant form. We analyze that text using a reception and intertextual approach. There receptive approach takes over the researcher role as the explicit reader and the role of the text as the real matter of the implicit reader role. The intertextual approach here means while takes over the role of other text as the understanding background of UUM. From the analytical receptivity we know that a receptive on structure language .and context has existed in the UUM text. The aspect receptivity signed by verse addition absorbed from Islamic laws, the pattern and the method of writing. The receptivity of the language as used in Islamic law as usual. The content receptivity signed by the influence and absorption from the Islamic law text existed in the syncretism laws. We know from the intertextual analysis, UUM text has intertext relation with Quran. 'Hadis/Prophet's tradition, and Ijmak/Consensus. In the other hand, from the two approaches We hope to know the Islamic law' contents which were absorbed into UUM, and the Islamic Laws' practiced by community of Malaka at that time. Finally, we shall know that the receptivity and the intertextual process in the UUM is the consequence and also the results of the diffusion. This diffusion took place the local culture was influenced by Hinduism-Buddhism and Islam. In this case involved some kinds of culture, one of them was language, system of religion and laws, etc.